x/9
2006-11-11 07:23:13
·
answer #1
·
answered by chaotique_79 2
·
1⤊
0⤋
(3x/18) - (x/18)
Here there are 3 lots of (x/18) subtracting 1 lot of (x/18).
3 lots of anything subtracting 1 lot of the same thing always equals 2 lots of the same thing.
For example, 3 (apples) - 1 (apple) = 2 (apples)
Or 3(Y) - (Y) = 2(Y)
Or 3(x/18) - (x/18) = 2(x/18)
(x /18) is called the common factor.
It's a thing on its own that is in both terms.
Another way of doing this is to take out the common factor, so you end up with a factorised form.
(3x/18) - (x/18) = (x/18)(3 - 1) = (x/18)(2) = 2x/18.
After you get 2(x/18), or 2x/18, there is another common factor of 2, which is both in the numerator and the denominator, because the denominator can be seen to equal 2 * 9.
So, 2x/18 = 2x/(2*9), which is (2/2) * (x/9).
2/2 = 1, so it can be eliminated,
which leaves the final answer as x/9.
2006-11-11 15:52:44
·
answer #2
·
answered by falzoon 7
·
1⤊
0⤋
3x/18-x/18=
2x/18=x/9
2006-11-11 16:27:57
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
Fractions - since the denominators are the same, combine the numerators
3x/18 - x/18 = 2x/18 = x/9
Don't forget to simplify, if possible
2006-11-11 15:27:31
·
answer #4
·
answered by kindricko 7
·
1⤊
0⤋
(3x/18)-(x/18) = (3x-x)/18= 2x/18 = x/9.
2006-11-11 15:27:05
·
answer #5
·
answered by Paritosh Vasava 3
·
1⤊
0⤋
Same denominator, so subtract numerators
2x/18 and reduce
x/9
2006-11-11 16:36:30
·
answer #6
·
answered by mom 7
·
1⤊
0⤋
2x/18 or x/9
2006-11-11 15:28:26
·
answer #7
·
answered by Chris E 3
·
1⤊
0⤋
(3x/18)-(x/18)=(3x-x)/18=2x/18=x/9
2006-11-11 18:05:37
·
answer #8
·
answered by yupchagee 7
·
0⤊
0⤋
look @ it this way: 3/18 x - 1/18 x =2/18x=1/9x or x/9!!!
2006-11-11 15:35:55
·
answer #9
·
answered by smilepalooza12 1
·
1⤊
0⤋
x/9
2006-11-11 17:29:24
·
answer #10
·
answered by J 6
·
0⤊
0⤋